MICHEL FOUCAULT DAN “STILISASI DIRI” - Konrad Kebung (Litbang STFT Widya Sasana Malang, 2016)
The paper discusses the rich philosophical thoughts of Michel Foucault, a 20th century French thinker and intellectual, from his early works (oeuvres) through his later works, which appeared shortly before his death. The writer presents Foucault’s many discourses on different topics and problems that reach its final project in the stylization of the self. This “self” should be built up continually, and this self and life should be re-evaluated or valorized throughout life. It is clear then that there is no stable subject or self. Instead it is always unstable that needs to be valorized on and on. Life is likely a work of art. Foucault also claims that the one who is able to care of him/herself will also be able to care for others.